2006
DOI: 10.2223/jped.1525
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of and variables associated with smoking in children and adolescents in the Maceió education system

Abstract: Objective: To identify the prevalence of smoking and the presence of variables associated with the habit in children and adolescents of both sexes, aged 7 to 17 years, resident in the city of Maceió. Methods:A cross-sectional epidemiological study of the student population of the both private and public education systems at elementary and high school level. Sample size was calculated based on the minimum predicted prevalence of a large number of variables, including smoking itself. Cluster sampling was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
1
7
1
9
Order By: Relevance
“…Our overall experimentation rate of 26.3%, and 44.3% among those who were 13 at baseline, appears comparable to rates reported elsewhere. In Brazil, 30% of 7 th to 10 th grade (39) and up to 50% of 15 to 16 year-old European students (40) report experimenting…”
Section: Discussionmentioning
confidence: 99%
“…Our overall experimentation rate of 26.3%, and 44.3% among those who were 13 at baseline, appears comparable to rates reported elsewhere. In Brazil, 30% of 7 th to 10 th grade (39) and up to 50% of 15 to 16 year-old European students (40) report experimenting…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that smoking behavior is influenced by gender and age [24, 25, 26], therefore both were included as control variables in the study. Age was entered in its continuous format.…”
Section: Methodsmentioning
confidence: 99%
“…Estudo recente no Sul do Brasil, mostrou uma maior prevalência do hábito de fumar no sexo feminino (Horta et al, 2007). Outro trabalho, realizado em Maceió, mostrou risco aumentado de o adolescente tornar-se tabagista após a experimentação do cigarro (Silva et al, 2006).…”
Section: Tabagismo Ativounclassified
“…Com relação ao tabagismo ativo na população estudada, a idade de início do hábito de fumar foi de 13-14 anos como observado em outros estudos (Malcon et al, 2003;Silva et al, 2006;Aburto Barrenechea et al, 2007). No entanto a prevalência de fumantes de 0,7% entre os adolescentes, foi menor que a observada em diferentes pesquisas, com valores de prevalência que variaram de 2,4 a 12,1% ( Stewien e Marcondes, 1979;Horta et al, 2001;Malcon et al, 2003;Silva et al, 2006;Aburto Barrenechea et al, 2007;Menezes et al, 2007).…”
Section: -Discussãounclassified
See 1 more Smart Citation